PENGARUH KOMPETENSI TERHADAP WITHDRAWAL BEHAVIOR PADA KSPPS PERAMBABULAN MAKMUR ABADI DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI - Ayu Diah; Ali Jufri; Puspa Dewi Yulianty (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to examine the effect of competence on withdrawal behavior among employees at KSPPS Perambabulan Makmur Abadi, with work engagement as a mediating variable. High competence is expected to reduce withdrawal behavior by enhancing employee work engagement. The study used a quantitative method with linear regression analysis and Sobel test to test the hypotheses. The results show that competence has a significant positive effect on work engagement, and work engagement has a significant negative effect on withdrawal behavior. Additionally, work engagement mediates the relationship between competence and withdrawal behavior. Therefore, increasing employee competence followed by enhanced work engagement can reduce withdrawal behavior, which could negatively affect organizational productivity. These findings provide important recommendations for organizations to develop employee competence through relevant training and create a work environment that fosters their engagement in tasks.